2010
DOI: 10.1182/blood-2009-07-231449
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-5 is bound onto the surface of rat reticulocyte exosomes and modulates vesicle uptake by macrophages

Abstract: Reticulocytes release small membrane vesicles termed exosomes during their maturation into erythrocytes. Exosomes are intraluminal vesicles of multivesicular endosomes released into the extracellular medium by fusion of these endosomal compartments with the plasma membrane. This secretion pathway contributes to reticulocyte plasma membrane remodeling by eliminating certain membrane glycoproteins. We show in this study that galectin-5, although mainly cytosolic, is also present on the cell surface of rat reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
222
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(233 citation statements)
references
References 52 publications
7
222
1
3
Order By: Relevance
“…The Galectin 5 pathway, in which this ␤-galactoside-binding lectin, present in the lumen of MVBs, is presumed to recruit various glycosylated proteins (19). In light of our results, this pathway would remain relatively constant during the different stages of maturation of the reticulocytes and would be responsible for the elimination of proteins that may well still have been needed at earlier stages, such as those involved in cell structure and motility.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The Galectin 5 pathway, in which this ␤-galactoside-binding lectin, present in the lumen of MVBs, is presumed to recruit various glycosylated proteins (19). In light of our results, this pathway would remain relatively constant during the different stages of maturation of the reticulocytes and would be responsible for the elimination of proteins that may well still have been needed at earlier stages, such as those involved in cell structure and motility.…”
Section: Discussionmentioning
confidence: 86%
“…The second route is associated with membrane lipid microdomains enriched in ceramides (17,18). The third route is initiated on the lumenal side of the endosomal compartment by aggregating factors such as lectins (19,20).…”
mentioning
confidence: 99%
“…31 Galectin is a type of lectin that shows affinity for b-galactoside. Extracellular gelectins cross-link cell surface and extracellular glycoproteins and may thereby modulate cell adhesion and induce intracellular signals.…”
Section: Exosomal Membrane Molecules and Immune Response Activationmentioning
confidence: 99%
“…As an important member of the galectin family, galectin-5 is unique for rats and present on the surface of reticulocytes and erythrocytes. Barrès et al [32] reported galectin-5 functionality in the exosomal sorting pathway during rat reticulocyte maturation. Reticulocyte count has been suggested to play a major role in anemic evaluation [33].…”
Section: Discussionmentioning
confidence: 99%